New records of Tachybaptus dominicus (Linnaeus, 1766) (Aves, Podicipedidae) south of its currently known distribution in Argentina - Castillo, Santiago (2019)
We report on 4 records of the Least Grebe, Tachybaptus dominicus (Linnaeus, 1766), to the south of its theoretical distributional limit in Córdoba Province, Argentina. In recent years, these records and others uploaded to citizen science platforms suggest that this species’ distribution extends south of its currently known range.